VAN BOUWKUNDE TOT ARCHITECTUUR: INSTITUTIONALISATION OF BUILDING ENGINEER AND ARCHITECT IN DUTCH-EAST INDIES, 1854-1942 - Mahatmanto
The establishment of the architectural professional institution in Indonesia is a significant historical event that has not been thoroughly examined. If the architectural profession is concerned with the presence of engineering specialists in the construction industry, then documenting the history of this profession must also include a historical examination of building engineering education throughout the time of Dutch colonialism. In order to fulfil this objective, it is necessary to provide a detailed account of the development of building engineering education in the Dutch East Indies, with a particular focus on the 19th century. At first, constructive education was mostly practiced within ethnic cultural groups throughout the archipelago. In addition to the customary technical training provided by and for indigenous populations, there is also training offered by Indo organisations and training arranged by the military. These three categories of technical training possess distinct objectives and training methodologies. It was not until the mid-19th century that people became aware of the necessity to have a comprehensive education, including elementary, secondary, and higher education, in order to be prepared for a vocation regardless of race. Political and economic stability are necessary for the smooth progress of colony development and the formalisation of professional education. Historical records on educational reform in the 19th and 20th centuries indicate the existence of two professional institutions in the field of architecture: VvBNI and NIAK. A study of the two professional organisations determined that the occupations of builders and architects played a crucial role in the initial stages of colonisation growth. Prior to the conclusion of the Dutch East Indies rule, the concept of the architectural profession, which involves the specialised activity of designing buildings, had not yet been established. The requirement for precision in defining the responsibilities of architects was established only after independence in order to refine their professional identity, which had been rather unclear in the preceding era, until the early 20th century, was still mixed with other engineering professions.